Black tea preserves intestinal homeostasis through balancing barriers and microbiota in mice - Shi, Yuxuan; Guo, Shasha; Zhou, Jihong; Xu, Ping; Wang, Yuefei (Frontiers in Nutrition, 2024)
Black tea, a beverage consumed worldwide, possesses favorable effects on gastrointestinal tract, including nourishing stomach and promoting digestion.Nevertheless, its specific effects on intestinal homeostasis remains inconclusive. Here, a dextran sulfate sodium (DSS)-induced colitis mouse model was employed to investigate the preventive potential of black tea against intestinal homeostasis disruption. The results showed that black tea-treated group significantly rescued the DSS-disrupted intestinal structure. It reduced the relative abundance of the pathogenic bacterium Turicibacter, while increased the abundance of beneficial bacteria norank_f_Muribaculaceae and restored the contents of short-chain fatty acids (SCFAs) such as acetate, propionate, and butyrate. It also protected the intestinal barrier by reducing the levels of immune response-related factors (e.g., TNF-α, IL-6, IL-1β) and increasing the expression of tight junction proteins (TJs) (e.g., ZO-1, occludin). Furthermore, black tea exhibited the capacity to suppress the expression of MMP-9 and ICAM-1, as well as to inhibit the activation of NF-κB signaling pathway.Collectively, our findings established a theoretical framework elucidating the mechanisms by which black tea preserves intestinal homeostasis.